Numerical and experimental study of ship-generated waves - Rodrigues, Sara (2021)
This paper presents the results of the numerical and experimental study on the propagation of ship-generated waves. In the numerical modified FUNWAVE code, which is able to reproduce most of the phenomena involved in wave propagation, the ship is represented by a moving pressure distribution function at the free surface. The experimental tests were carried out with a ship model at a 1: 50 scale that moving at constant speed across a constant depth region. The values of wave heights obtained in the scale ship model 1: 50 were used to compare with the predictions of wave heights provided by the numerical code. The comparison of the results obtained by the numerical code and the experimental tests shows very similar values for the maximum wave height.